Pengaruh Profitability, Leverage, Liquidity, Dan Good Corporate Governance Terhadap Financial Distress - Achyani, Marleny Nur; Kusumawati, Eny (Politeknik Negeri Ambon, 2023)
Financial distress is a condition of continuous financial decline in a company, caused by decision-making errors, management weaknesses, and lack of monitoring of inappropriate financial performance, which is a potential indicator of bankruptcy. This research aims to analyze the influence of profitability, leverage, liquidity, and good corporate governance on financial distress in non-financial companies on the Indonesia Stock Exchange for the 2020-2022 period. The sampling technique used in this research was purposive sampling. A total of 771 companies have met the criteria as observation units. The analytical method used is multiple linear regression analysis based on classical assumptions. The research results reveal that profitability and leverage affect financial distress, while liquidity, the independent board of commissioners, and the audit committee do not affect financial distress.